WILL ARTIFICIAL INTELLIGENCE REPLACE DOCTORS AND TEACHERS BY 2035? EVIDENCE-BASED ANALYSIS FROM MEDICINE AND EDUCATION - Abbasi, Munir Ahmad; Khan, Shahbaz Ali (Journal of Ayub Medical College Abbottabad, 2025)
Predictions that artificial intelligence will replace doctors and teachers within the next decade have gained significant attention, yet a critical review of the scientific and policy literature from 2019 to 2024 reveals a more nuanced reality. Recent advances in AI have transformed diagnostic, predictive, and administrative functions in both medicine and education, often surpassing human performance in narrowly defined, data-rich tasks. However, core professional competencies—such as ethical judgment, empathy, contextual understanding, and the ability to foster human relationships—remain beyond the reach of current AI technologies. Ongoing challenges include the explainability of AI models, data privacy, legal accountability, and alignment with human values. Policy frameworks from leading organizations consistently recommend human-AI collaboration rather than replacement. The evidence indicates that while AI will continue to automate routine functions and reshape aspects of both professions, the essential roles of doctors and teachers are unlikely to be displaced in the foreseeable future. Instead, the future of medicine and education depends on responsible integration, robust oversight, and a focus on preserving the uniquely human elements of care and learning.